Greek library : the Konstantinos Sp. Staikos book collection henceforth the Alexander S. Onassis public benefit foundation library - Παναγιωτόπουλος, Νίκος; Sloman, Doolie; Πετσίνη, Πηνελόπη (Άτων, 2010)
Τhe genesis of the formation regarding the collection dates 1970s. At that time there was no specific reasoning behind it, and the books acquired during that period were of a varied content of subjects: historical, literary and encyclopaedic. However, from the middle of that decade, through associating with the people of the world of books - such as Maria Koutarelli, who inherited and accrued the collection of books and manuscripts of Spyros Loverdos - my bib-liophilic interests changed radically. In those years also, the Hellenike Etairia Bibliophilon (Hellenic Bibliophile Society - 1975 Statute) was established, founding members of which were eminent personalities of the intellect and the arts, bibliophiles and collectors, under the Honorary Presidency of Constantinos Tsatsos. Among the members of the Society, I should like to mention Loukia Droulia, Ekaterini Koumarianou, Hadjikyriakos Gkikas, Rena Andreadi, Manos Haritatos and, of course, Yiannis Phikioris with whom I pursued another parallel course of bibliophily, at the time when he undertook the presidency of the Hellenic Bibliophile Society. It was a relationship of esteem and friendship, lasting to this day.